Estudo tridimensional da vibração induzida por vórtices sobre um cilindro rígido elasticamente apoiado através da solução numérica das equações de Navier-Stokes - Silva, Thiago Santos Freitas Castro (2019)
The effects of Vortex Induced Vibration (VIV) have great importance in several areas of Engineering. In oil exploration, for example, risers are structures commonly subject to this type of phenomenon and can suffer damage due to the oscillations caused by it. Vortex Induced Vibration of a rigid circular cylinder elastically mounted with one degree of freedom was studied and the drag and lift coefficients, frequency, amplitude and phase angle responses, were obtained for a reduced velocity range of 2 to 12. The numerical solution for the three-dimensional, slightly compressible Navier-Stokes equations was obtained using the Finite Volume Method and Large Eddy Simulation. The 3rd order Runge-Kutta method was used to perform the march in time. A curvilinear mesh, body fitted with 8 million knots was used in the simulations. Although the maximum response amplitude obtained was lower than expected, the present work was able to successfully capture the lock-in frequency, the phase angle change with the increase in reduced velocity and the 2S and 2P vortex shedding modes, besides allowing the visualization of the three-dimensional swirling wake and its properties.